2015
DOI: 10.1073/pnas.1500223112
|View full text |Cite
|
Sign up to set email alerts
|

Selective resistance to the PARP inhibitor olaparib in a mouse model for BRCA1-deficient metaplastic breast cancer

Abstract: Metaplastic breast carcinoma (MBC) is a rare histological breast cancer subtype characterized by mesenchymal elements and poor clinical outcome. A large fraction of MBCs harbor defects in breast cancer 1 (BRCA1). As BRCA1 deficiency sensitizes tumors to DNA cross-linking agents and poly(ADP-ribose) polymerase (PARP) inhibitors, we sought to investigate the response of BRCA1-deficient MBCs to the PARP inhibitor olaparib. To this end, we established a genetically engineered mouse model (GEMM) for BRCA1-deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 37 publications
2
71
0
Order By: Relevance
“…We postulate the observed lack of significant pharmacologic blocking of olaparib is due to differences in pharmacokinetics between olaparib and [ 125 I] KX1 , resulting in lower tumor uptake of the competing olaparib. Olaparib has very quick clearance from tissues due to p-glycoprotein efflux mechanisms and fast renal clearance (25, 26). Autoradiography of tumors from HCC1937 and MDA-MB-231 xenograft models confirmed the small differences observed in vivo (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We postulate the observed lack of significant pharmacologic blocking of olaparib is due to differences in pharmacokinetics between olaparib and [ 125 I] KX1 , resulting in lower tumor uptake of the competing olaparib. Olaparib has very quick clearance from tissues due to p-glycoprotein efflux mechanisms and fast renal clearance (25, 26). Autoradiography of tumors from HCC1937 and MDA-MB-231 xenograft models confirmed the small differences observed in vivo (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies in prostate and other cancer types, have also reported PARP inhibitor resistance as a result of EMT, which is often present in cancers that acquire resistance to treatment [6466]. In general, EMT is described as reprogramming of terminally differentiated cells into more mesenchymal-type cells [67].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor burden was calculated as the ratio between the total tumor area and the area of the whole mammary gland using ImageJ software version 1.4.3.67. Immunohistochemical stainings were processed as described (Doornebal et al 2013;Henneman et al 2015). Antibody details and antigen retrieval methods are described in Supplemental Table S1.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%